2019
DOI: 10.1136/bmjpo-2019-000465
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic and clinical risk factors for paediatric typical haemolytic uraemic syndrome: retrospective cohort study

Abstract: ObjectivesHaemolytic uraemic syndrome (HUS) following Shiga toxin-producing Escherichia coli (STEC) infection is the the most common cause of acute renal failure among children in the UK. This study explored differential progression from STEC to HUS by social, demographic and clinical risk factors.MethodsWe undertook a retrospective cohort study linking two datasets. We extracted data on paediatric STEC and HUS cases identified in the Public Health England National Enhanced Surveillance System for STEC and Bri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 27 publications
0
11
1
Order By: Relevance
“…Adjusted odds of chronic kidney failure in this study were also lower among urban cases compared to rural cases. Several studies have shown that rural populations have higher exposure to STEC ( 21 , 22 ) and consequently are at higher risk of HUS ( 23 ), although these results are not consistent with other studies ( 24 ). While sample size (74 HUS cases from among 71 families) likely limited this study to detecting only large effects, it is notable that the sample size in this study is larger than most cohort studies on LTHOs of HUS which frequently consist of <50 cases ( 4 ).…”
Section: Discussioncontrasting
confidence: 58%
“…Adjusted odds of chronic kidney failure in this study were also lower among urban cases compared to rural cases. Several studies have shown that rural populations have higher exposure to STEC ( 21 , 22 ) and consequently are at higher risk of HUS ( 23 ), although these results are not consistent with other studies ( 24 ). While sample size (74 HUS cases from among 71 families) likely limited this study to detecting only large effects, it is notable that the sample size in this study is larger than most cohort studies on LTHOs of HUS which frequently consist of <50 cases ( 4 ).…”
Section: Discussioncontrasting
confidence: 58%
“…During the surveillance period, <6% of cases detected and diagnosed as STEC-positive developed HUS, which is lower than the 15% reported by Tarr et al and 20% by Adams N et al, although the latter data relate to STEC O157 infections only [2,27]. Not all the patients with STEC infection develop BD, and this finding may partly explain this difference.…”
Section: Discussionmentioning
confidence: 63%
“…Data produced in the present study show that 70% of STEC positive cases in the pediatric population occurred in the 0-4 years age group. In the EU, almost one-third of all confirmed STEC cases have been reported in children aged <4 years, which is the age group with the highest reporting rate (8.9 cases/100,000 population), confirming that very young children are at a higher risk of infection than people of other ages [19,26,27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cumulatively, young children (<5 years) and the older subpopulation (>65 years) accounted for 56.7% (n = 1,563) of confirmed sporadic infections. Both of these subpopulations are known to be immunologically vulnerable and exhibit higher incidence rates of infection and severe sequelae (29,30). Younger cohorts especially are at increased risk of infection caused by frequent contact with other children of a similar age, and also pose a risk as a source of infection associated with increased contact with adults, particularly among the 30-39 year age group (31,32).…”
Section: Discussionmentioning
confidence: 99%